The Effects of Story Recitation for Young Language Learners - Anesti Budi Ermerawati (Universitas Pendidikan Mandalika, 2018)
This article discusses the effects of reciting English story in a way to prepare a storytelling competition in a private elementary school. Initially forced to use the method, the young language learners (YLL) gradually came to appreciate it. The practice enabled them to construct the story comprehensively, to improve pronunciation, to motivate their peers to tell the story confidently, and to develop the habit of attending the details of language in the context of language input. To investigate how beneficial the English story recitation is, I use interview to examine teacher’s perceptions and experiences about story recitation and its effect on language development. I will also investigate how story recitation is used and its effects in an EFL (English as a foreign language) context. The paper concludes that such practice enhances YLL’s noticing and rehearsal and later it facilitates second language acquisition. Therefore, teachers are suggested to have a positive attitude towards English story recitation for young language learners.